2018
DOI: 10.1016/j.ebiom.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Goal Directed and Self-Control Systems in Bulimia Nervosa: An fMRI Study

Abstract: BackgroundBinge eating is apparently the opposite of the strict control over food intake typically set by “maladaptive dieters”. Using functional magnetic resonance imaging (fMRI), we investigated the role of goal-directed behaviors, and the related use of self-control, in binge-related food choices in patients with Bulimia Nervosa (BN).MethodWhile undergoing fMRI, women aged 18–35 with BN (N = 35) and healthy control women (N = 26) rated foods for healthiness and tastiness and then made food choices on a 5 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…Similarly, another study found that subthreshold BN was associated with increased amygdala connectivity with the insula and putamen during anticipation of tasting a milkshake, highlighting the importance of the insula in binge eating pathology ( Bohon and Stice, 2012 ). Finally, greater connectivity between the dlPFC and vmPFC was associated with more frequent selection of unhealthy calorie dense foods among individuals with BN, a relationship that was not apparent among healthy individuals ( Neveu et al , 2018 ). Together, these findings suggest that binge eating psychopathology is associated with differences in network organization and regions that support reward valuation and salience detection during the processing of food cues.…”
Section: Relationship Between Disordered Eating Behaviors and Functiomentioning
confidence: 99%
“…Similarly, another study found that subthreshold BN was associated with increased amygdala connectivity with the insula and putamen during anticipation of tasting a milkshake, highlighting the importance of the insula in binge eating pathology ( Bohon and Stice, 2012 ). Finally, greater connectivity between the dlPFC and vmPFC was associated with more frequent selection of unhealthy calorie dense foods among individuals with BN, a relationship that was not apparent among healthy individuals ( Neveu et al , 2018 ). Together, these findings suggest that binge eating psychopathology is associated with differences in network organization and regions that support reward valuation and salience detection during the processing of food cues.…”
Section: Relationship Between Disordered Eating Behaviors and Functiomentioning
confidence: 99%
“…A growing literature is investigating brain processes in BN compared to HC alone or in conjunction with AN subtypes. For example, compared to HC, BN exhibit (a) higher medial PFC activation to overweight body images (Spangler & Allen, ); (b) lower anterior cingulate cortex (ACC), occipital, and orbitofrontal activation to desirable food cues following a stress induction (Collins et al, ); and (c) lower health appraisal of food despite similar ventromedial PFC activation and tastiness appraisals when making desirable food choices (Neveu et al, ). Taken together, these findings are consistent with heightened brain resources devoted to social comparison in BN as well as lowered food‐related conflict in the face of stress.…”
Section: Resultsmentioning
confidence: 99%
“…Makan berlebihan tersebut merupakan istirahat dalam kontrol ketat atas asupan makanan penderita bulimia nervosa (13).…”
Section: Abstrakunclassified